PENGGUNAAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DALAM ANALISA PEMILIHAN MEDIA PEMBELAJARAN E-LEARNING SEBAGAI SARANA PENDUKUNG PEMBELAJARAN (STUDI KASUS SMKN 2 PADANG) - W, Mitta Natalia (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
In the current era of globalization, any information can be easily and quickly obtained, eitherfrom a credible source or not. This information is of course due to a bridging technology, thistechnology is often referred to as Information and Communication Technology or ICT. Rightnow with ICT not only exchange information that is easy to do but has already become themedium of electronic transaction between sellers and buyers, or between firms. So it is withlearning, the learning process can be done trough electronic media, called e-learning. SMKN2 Padang will implement e-learning learning system as a means of supporting learning inorder to improve the quality of the learning process is good. The purpose of learning activitieswill determine the media used, either stand alone or a combination of various media. Onemethod that can be used as a decision making process in determining which media will beused is by using the Analytic Hierarchy Process, known as the Analytical Hierarchy Process(AHP). Tests carried out using the software Superdecision 1.6 was used to compute theproblem solving with AHP.Kata Kunci: E – learning, Analytical Hierarchy Process (AHP).